Perception of Veterinarians towards the Services Rendered by Animal Husbandry Assistants through Farmers Assurance Centers (Rythu Bharosa Kendras) - Priya Katti, Ranjani; Pulla, Sireesha; Bodapati, Subrahmanyeswari; Pothanaboina, Guru Vishnu; Lakshmi Bethapudi, Rajya; Deeptimahanti, Saisri (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Livestock farming plays a pivotal role in India’s agricultural sector, contributing significantly to the nation’s GDP. To enhance the quality of services for livestock farmers, the state government of Andhra Pradesh has established Rythu Bharosa Kendras (RBKs) or what is called Farmers Assurance Centers (FACs) at every Panchayat. The study focuses on veterinarians’ perception on the services provided by Animal Husbandry Assistants (AHAs) through RBKs. Data was collected from 45 veterinarians from nine districts using structured interview schedule and statistical analysis was employed to assess the perception of veterinarians. The findings revealed that significant proportion of veterinarians had medium level of perception. The challenges faced by AHAs identified were inadequate knowledge and skills and limited hands-on experience. It is concluded that the State Animal Husbandry Department should organize refresher training programs for Animal Husbandry Assistants and Veterinarians should assess AHAs performance regularly and guide them in providing better services.